2010
DOI: 10.1016/j.jasms.2009.11.010
|View full text |Cite
|
Sign up to set email alerts
|

A tuning method for electrically compensated ion cyclotron resonance mass spectrometer traps

Abstract: We describe a method for tuning electrically compensated ion cyclotron resonance (ICR) traps by tracking the observed cyclotron frequency of an ion cloud at different oscillation mode amplitudes. Although we have used this method to tune the compensation voltages of a custom-built electrically compensated trap, the approach is applicable to other designs that incorporate electrical compensation. To evaluate the effectiveness of tuning, we examined the frequency shift as a function of cyclotron orbit size at di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…The approach also minimizes frequency shifts due to ion-ion interactions, by enabling the use of increased excitation radii [7]. The goal can be achieved by creating a potential distribution close to the quadrupolar potential [3,4,20]:…”
Section: Theorymentioning
confidence: 99%
See 3 more Smart Citations
“…The approach also minimizes frequency shifts due to ion-ion interactions, by enabling the use of increased excitation radii [7]. The goal can be achieved by creating a potential distribution close to the quadrupolar potential [3,4,20]:…”
Section: Theorymentioning
confidence: 99%
“…The radial electric field distribution of the OC-7S cell was also compared with that of the ring [3,4] and leaf [5] cells, as described below.…”
Section: Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…This ICR cell was used, among others, for the analysis of bovine serum albumin mentioned earlier. The compensated ICR cell introduced by Gabrielse et al [19] for high-accuracy isotope mass measurement has been extended to analytical FT-ICR by Tolmachev et al [20] and Brustkern et al [21], who showed that it eliminates harmonics in the signal [16]. An asymmetric variation on this geometry in which the excitation and detection plates do not have the same geometry was developed by Kaiser et al [22] for complex mixtures.…”
Section: Introductionmentioning
confidence: 99%